How May â€œAIâ€ Help You? Analyzing the Role of AI-Backed Chatbot Interactions in Customer Services - Mahajan, Sunanjita; Gupta, Mansi; Chauhan, Vinay (Indian Journal of Marketing, 2025)
Purpose : The paper empirically investigated the impact of the interaction between AI-enabled chatbots and consumers on engagement dimensions and engagement outcomes in e-commerce platforms. The study aimed to understand the outcomes that can be derived from the interactions during customer services to help marketers leverage AI technologies efficiently. Design : Convenience sampling was employed to collect 311 cross-sectional data, which was analyzed through structural equation modeling using AMOS to test the hypotheses. Findings : The results revealed that AI-backed chatbot interaction is a multidimensional construct that significantly and positively impacted all customer engagement dimensions; however, it also reported that AI-enabled interaction failed to induce advocacy intention among consumers. Furthermore, the results unveiled a significant mediating role of affective and behavioral engagement in chatbot interaction and advocacy intention relationship, whereas the mediating effect of cognitive engagement was not supported. Research Implications : The results extended practical and theoretical implications by identifying the dimensions defining AI-backed chatbot interaction and investigating its impact on customer outcomes. It highlighted the role and limitations of AI-based chatbots and underscored the need for broader yet cautious implementation of such technologies in generating favourable outcomes in customer service systems. Originality : The study uncovered the role of chatbot interactions in driving cognitive, affective, and behavioural engagement and customer advocacy. It is one of the few studies that identified and acknowledged the importance of integrating these chatbots into customer services, along with the limitations that accompany it.